Membangun Aplikasi E-Commerce Berbasis Web Pada Toko Oleh-Oleh Khas Prabumulih - Dwintara, Ivan Mei (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
A typical prebumugift shop is a typical prabumufood shop of the prabumucities whose sales are still manual and the many buyers still haven't known of the pre-duduble gift shop. This research is aimed at designing and developing service systems. The advanced application development method consists of the requireplanning, the design and application process. The language phpmysql is a baseline optioning that allows for select data or data entry that might be easily worked on automatically.